2019
DOI: 10.3390/nano9030439
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Remediation Applications of Carbon Nanotubes and Graphene Oxide: Adsorption and Catalysis

Abstract: Environmental issues such as the wastewater have influenced each aspect of our lives. Coupling the existing remediation solutions with exploring new functional carbon nanomaterials (e.g., carbon nanotubes, graphene oxide, graphene) by various perspectives shall open up a new venue to understand the environmental issues, phenomenon and find out the ways to get along with the nature. This review makes an attempt to provide an overview of potential environmental remediation solutions to the diverse challenges hap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 164 publications
0
46
0
Order By: Relevance
“…The CNT- and graphene-modified electrodes were superior to the untreated carbon felt electrodes. Wang et al indicated that CNTs exhibited high adsorption capacities [7]. Dhand et al added CNTs to a PVDF membrane and the contact angle decreased from 103.6° to 88° [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNT- and graphene-modified electrodes were superior to the untreated carbon felt electrodes. Wang et al indicated that CNTs exhibited high adsorption capacities [7]. Dhand et al added CNTs to a PVDF membrane and the contact angle decreased from 103.6° to 88° [25].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they can assist in electron transfer. Wang et al indicated that the adsorption capacity of multi-wall carbon nanotubes (MWCNTs) was higher than that of activated carbon (AC) and that the surfaces of CNTs promoted the adsorption of hydrocarbons; therefore, they were suitable for treating contaminants [7]. Graphene has a hexagonal honeycomb lattice arrangement (single-layer 2D crystal film) formed from carbon atoms in the sp 2 orbital.…”
Section: Introductionmentioning
confidence: 99%
“…For example, graphene oxide (GO) has been verified; it has a large specific surface area, and there are various oxidizing functional groups (e.g., hydroxyl, carboxyl, and epoxy) in its structure. Additionally, it exhibits good dispersibility and an excellent adsorption force in water [27,28]. The most significant technical challenge of applying GO for adsorption is the difficulty of solid-liquid separation after adsorption; the separation is performed with ultrahigh-speed centrifuges, but it takes a long time to collect the GO, which is highly dispersed in water [29].…”
Section: Introductionmentioning
confidence: 99%
“…These properties are mainly originated by their low-dimensionality (1D, 2D) and high surface-to-volume ratio as well as their π-conjugated surface [8], which have propelled their incorporation into a wide range of functional systems where they usually play a central role. The usage of these nanostructures commonly takes advantage of one or more of the Nanomaterials 2020, 10, 614 2 of 13 different properties they possess, for instance, as nanometric supports for heterogeneous catalysts [9][10][11], optical or electrochemical transducers in sensors and biosensors [12][13][14][15], mechanical reinforcement or electrical percolation modulation in polymer nanocomposites [16][17][18][19][20], nanoscale-enhanced radiosensitization and drug delivery in cancer therapy and tumor bioimaging [21][22][23], among others. However, in order to provide them with the additional features required for a particular purpose (catalytic activity, ion recognition, stimuli responsiveness, etc.…”
Section: Introductionmentioning
confidence: 99%